(untitled) (Al-Aasar, 2025)
The Ahmadiyya Movement, founded by Mirza Ghulam Ahmad of Qadian (1835–1908) in late nineteenth-century British India, presents a unique theological understanding of divine revelation (ilhām). Originating as a revivalist reform within Islam, the movement later articulated a distinctive doctrine of revelation that redefined the relationship between God and humanity in the post-prophetic age. Mirza Ghulam Ahmad claimed to receive direct divine inspiration, considering it the continuation of a spiritual communication (mukālama wa mukhātaba ilāhiyya) that remains possible for the righteous even after the finality of prophethood. According to Ahmadi theology, revelation is of two kinds: (1) wahy tashri (legislative revelation), which ended with the Prophet Muhammad ﷺ, and (2) wahy ghayr tashri (non-legislative revelation), which continues as divine guidance to saints and reformers. Mirza Ghulam Ahmad located his own experiences within the latter category, describing them as direct divine speech revealed inwardly without mediation. His numerous writings such as Barāhīn-e-Ahmadiyya, Ḥaqīqat al-Waḥy, and Tadhkirah record hundreds of such revelations in Arabic, Urdu, and Persian, which he regarded as authentic divine communications. This doctrine stands in theological tension with orthodox Islam’s principle of khatm al-nubuwwa (finality of prophethood), as mainstream scholars regard any post-prophetic claim to revelation as incompatible with Islamic orthodoxy. Nevertheless, the Ahmadi understanding of revelation emphasizes a living, experiential relationship with God, interpreting ilhām as a mystical dialogue rather than legislative prophecy. In the broader intellectual history of South Asian Islam, the Ahmadi concept of revelation occupies a pivotal place in debates surrounding spiritual authority, modernity, and religious experience in colonial and postcolonial contexts.